(1177) Agricultural pricing and price theory تسعير المنتجات الزراعية ونظرية الأسعار - Werner Wunderliceh (معهد التخطيط القومي, 2026)
ملخص This academic study examines the mechanisms and structural dynamics involved in establishing uniform agricultural prices in the German Democratic Republic (GDR) during its transition toward large-scale cooperative production and industrialization. The text evaluates the shortcomings of the initial two-level price system, explaining how its failure to reflect socially necessary labor costs caused economic imbalances, thereby necessitating a historical shift toward unified pricing systems for both crop and livestock sectors. Methodologically, the study utilizes Marxist economic theory, particularly the concept of differential rent, to construct its pricing models. Through detailed empirical formulations for commodities like rye, potatoes, cattle, and milk, the paper demonstrates that uniform prices were indexed against production costs incurred under the least favorable natural soil conditions. This strategic baseline ensured that agricultural cooperatives operating under suboptimal geographical conditions could recover expenditures, realize net profits, and sustain extended reproduction. The analysis highlights the socio-political dimensions of agrarian pricing, asserting that socialist pricing is fundamentally a "class policy" designed to fortify cooperative frameworks and stabilize agrarian incomes relative to industrial wages. The study concludes by emphasizing that comprehensive central planning and social control remain vital to managing the structural gap arising from consumer food subsidies and navigating rapid scientific-technological advancements in modern industrialized farming. تُناقش هذه الدراسة التحليلية آليات وهياكل تحديد الأسعار الزراعية الموحدة في جمهورية ألمانيا الديمقراطية (GDR) خلال مرحلة التحول نحو الإنتاج التعاوني واسع النطاق وتصنيع القطاع الزراعي. تبحث الدراسة في إخفاق نظام الأسعار ثنائي المستوى (Two-level price system) الذي طُبق في البداية، وتوضح كيف أدى إلى تشوهات اقتصادية لعدم عكسه التكاليف الاجتماعية الضرورية، مما استوجب الانتقال التاريخي لتوحيد الأسعار لكل من الإنتاج النباتي والحيواني من الناحية المنهجية، يرتكز الإطار النظري للبحث على المفهوم الماركسي للريع التفاضلي (Differential Rent). وتُظهر الجداول الرياضية التطبيقية (مثل تحديد أسعار المحاصيل كالقمح والبطاطس، والإنتاج الحيواني كالماشية والألبان) أن الدولة اعتمدت على حساب تكاليف الإنتاج في الأراضي ذات الخصوبة الطبيعية الأقل (الأكثر سوءًا) كقاعدة أساسية لتحديد مستوى الأسعار الموحدة، وذلك لضمان استمرار التعاونيات الواقعة في بيئات زراعية صعبة وتغطية تكاليفها وتحقيق فائض يُمكنها من التجديد الذاتي تُبرز الدراسة الأبعاد السياسية والاجتماعية لسياسة الأسعار؛ حيث تؤكد أن تسعير المنتجات في الاقتصاد الاشتراكي ليس مجرد مسألة حسابية بل هو "سياسة طبقية" تهدف لدعم صغار ومتوسطي الفلاحين وتحقيق الاستقرار في دخول العاملين بالقطاع مقارنة بالقطاعات الصناعية. وتختتم الأطروحة بالإشارة إلى حتمية التخطيط المركزي الشامل والرقابة المجتمعية لمواجهة التحديات الهيكلية الناتجة عن دعم أسعار السلع الغذائية الاستهلاكية للمواطنين، وضمان مواكبة الثورة العلمية والتكنولوجية في مجالي الإنتاج النباتي والحيواني. . .